(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Injury is any harm caused illegally to a person, which may be caused by any mechanical force which results in a break in natural continuity of any tissue.Each and every injury as its own medico-legal importance which is the key in interpretation of specific injury. Thus every medical student must be clear about this, which helps in concluding different injuries as every medical practitioner has to deal with injuries throughout their life. This can be dealt only when there is proper knowledge and awareness about different injuries in medical field. Objective: This study was done to study knowledge and awareness of medical students about injuries in forensic perspective. Materials and Method: It is a cross-sectional study done at Saveetha Medical College, Chennai, Tamil Nadu. Students of 2nd, 3rd, and 4th year M.B.B.S participated after giving informed consent. 115 students participated in the study. Questionnaire containing 20 questions were distributed and responses were obtained and analyzed. Results: Out of 115 students, 95% of the students had basic knowledge on injuries. Though awareness was present, there was minimal lack in certain areas such as knowledge on contusions, grievous hurt and differentiating cut and chop wounds. Conclusion: The knowledge and awareness on various injuries is very important for every medical student and practitioner for recognizing and differentiating it. So students should gain more knowledge and awareness on injuries.